BLACK BOX TESTING IN THE ACCESS BY KAI APPLICATION USING BOUNDARY VALUE ANALYSIS AND GRAPH-BASED TESTING - Irnayanti Dwi Kusuma; I Gusti Lanang Agung Oka Cahyadi Pradipta; Umi Laili Yuhana (INFOTECH journal, 2024)
The Access by KAI application is an application that focuses on the process of ordering train tickets via internet technology. The aim of making this application is to help make it easier for people to order train tickets. By creating this application, it is hoped that it can increase train ticket sales and make it easier for people to order train tickets online. Each feature of this application was subject to testing to ensure that it was running according to the expected functionality. The testing of a Black Box Testing using Boundaries Value Analysis and Graph-Based Test on the Access by KAI has success percentage 78%.